Strengthening Character Development Through Moral Values Education in Early Childhood Education - Darmawati Taro; St. Warda Hanafie Das; Muhammad Nurmaallah; Sumadin Sumadin; Andi Abd Muis (CV. Gerasi Insan Nusantara, 2026)
Moral values education plays a crucial role in fostering children's character development during early childhood, a critical period for establishing lifelong moral behaviour. Although previous studies have emphasized the importance of character education, limited empirical evidence explains how moral values are systematically integrated into early childhood learning through collaboration among teachers, families, and schools. This study aims to examine the implementation of moral values education and its contribution to children's character development in an Indonesian kindergarten. A qualitative case study design was employed at TK Pertiwi 1 Cakke, Enrekang Regency, Indonesia. Data were collected through classroom observations, semi-structured interviews with the principal and teachers, and document analysis. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña, supported by triangulation to ensure trustworthiness. The findings indicate that moral values, including honesty, responsibility, empathy, cooperation, respect, and generosity, are effectively integrated into daily learning through teacher role modelling, play-based learning, storytelling, collaborative activities, and continuous habituation. The implementation is further strengthened by active parental involvement and a supportive school environment, although inconsistent family support and limited instructional resources remain significant challenges. This study contributes to the literature by proposing a holistic framework that integrates classroom instruction, school culture, teacher exemplification, and family engagement as interconnected components for strengthening character development in early childhood education.